Aluminum alloy forgings and manufacturing method thereof
Patent Information
- Application Number
- JP2020206757
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-14
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-12-14
AI Technical Summary
【0017】 [1]の発明によれば、合金組成の限定と共に、アルミニウム合金鍛造品の断面組織を1000倍の倍率で観察した視野面積1.5815mm2に存在する短軸が0.5μm以上の金属間化合物Mg2Siの個数が100個以下であることで、常温において優れた機械的特性を有すると共に、再結晶粒が発生し難いAl-Mg-Si系アルミニウム合金鍛造品を得ることができる。
Smart Images

Figure 0007643025000003 
Figure 0007643025000004 
Figure 0007643025000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an Al-Mg-Si aluminum alloy forging having excellent mechanical properties and a method for producing the same.
[0002] In this specification, the term "FE-SEM" means a field emission scanning electron microscope. [Background technology]
[0003] In recent years, aluminum alloys have been increasingly used as structural components for various products, taking advantage of their light weight. For example, high-tensile steel has been used for the suspension and bumper parts of automobiles, but in recent years, high-strength aluminum alloy materials have come to be used. For automobile parts, such as suspension parts, iron-based materials were used exclusively, but they are now often replaced by aluminum or aluminum alloy materials, mainly for the purpose of reducing weight.
[0004] These automobile parts require excellent corrosion resistance, high strength, and excellent workability, so Al-Mg-Si alloys, especially A6061, are widely used as aluminum alloy materials. In order to improve the strength of these automobile parts, they are manufactured by forging, which is one type of plastic processing, using the aluminum alloy material as a processing material. Recently, due to the need to reduce costs, suspension parts obtained by forging cast members as they are without extrusion and then subjecting them to T6 treatment have begun to be put to practical use, and development of high-strength alloys to replace the conventional A6061 is underway for the purpose of further weight reduction (see Patent Documents 1 to 3 below). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 5-59477 [Patent Document 2] Japanese Patent Application Publication No. 5-247574 [Patent Document 3] Japanese Patent Application Publication No. 6-256880 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the above-mentioned high-strength Al-Mg-Si alloys have a problem in that the processed structure recrystallizes during the forging and heat treatment processes, resulting in the generation of coarse crystal grains, making it impossible to obtain a sufficiently high strength. Therefore, some alloys have been designed to prevent recrystallization by adding Zr to prevent the generation of coarse recrystallized grains (see Patent Documents 1 and 2 above).
[0007] Although the addition of Zr is effective in preventing recrystallization, it has the following problems.
[0008] (1) The addition of Zr weakens the effect of refining the crystal grains of the Al-Ti-B alloy, coarsening the crystal grains of the ingot itself, leading to a decrease in the strength of the processed product (forged product) after plastic processing.
[0009] (2) The effect of refining the crystal grains of the ingot itself is weakened, so that the ingot is more likely to crack, the number of internal defects increases, and the yield decreases.
[0010] (3) Zr forms compounds with Al-Ti-B alloys. These compounds accumulate at the bottom of the furnace in which the molten alloy is stored, contaminating the furnace. In addition, these compounds also crystallize out as coarse particles in the produced ingots, reducing their strength.
[0011] Thus, although the addition of Zr is effective in preventing recrystallization, there is a problem in that it is difficult to maintain stability in strength.
[0012] The present invention has been made in consideration of the above technical background, and has an object to provide an Al-Mg-Si aluminum alloy forging that has excellent mechanical properties at room temperature and is less susceptible to the generation of recrystallized grains, and a manufacturing method thereof. [Means for solving the problem]
[0013] In order to achieve the above object, the present invention provides the following means.
[0014] [1] An aluminum alloy forging containing 0.15% by mass to 1.0% by mass of Cu, 0.6% by mass to 1.3% by mass of Mg, 0.60% by mass to 1.45% by mass of Si, 0.03% by mass to 1.0% by mass of Mn, 0.2% by mass to 0.4% by mass of Fe, 0.03% by mass to 0.4% by mass of Cr, 0.012% by mass to 0.035% by mass of Ti, 0.0001% by mass to 0.03% by mass of B, a Zn content of 0.25% by mass or less, a Zr content of 0.05% by mass or less, and the balance being Al and unavoidable impurities, The cross-sectional structure of the aluminum alloy forging was observed at a magnification of 1000 times, with a field area of 1.5815 mm 2 The aluminum alloy forging is characterized in that the number of intermetallic compounds Mg2Si having a minor axis of 0.5 μm or more present in the forging is 100 or less.
[0015] [2] A method for producing an aluminum alloy forging according to the preceding paragraph 1, comprising the steps of: a molten metal forming step for obtaining a molten metal; a casting step of obtaining a casting by casting the molten metal obtained in the molten metal forming step; a homogenization heat treatment step in which homogenization heat treatment is performed on the casting obtained in the casting step; A forging process for obtaining a forged product by forging the cast product after the homogenization heat treatment process; a solution treatment step of subjecting the forged product obtained in the forging step to a solution treatment; a quenching treatment step of quenching after the solution treatment step; and an aging treatment step of subjecting the forged product after the quenching treatment step to aging treatment.
[0016] [3] The homogenization heat treatment step is a homogenization heat treatment step in which the casting obtained in the casting step is held at a temperature of 370°C to 560°C for 4 hours to 10 hours, The forging process is a process of forging the casting after the homogenization heat treatment process at a heating temperature of 450°C to 560°C. The solution treatment step is a step of heating the forged product obtained in the forging step from 20°C to 500°C at a heating rate of 5.0°C / min or more, and then holding the product at 530°C to 560°C for 0.3 hours to 3 hours. In the quenching treatment process, the entire surface of the forged product is brought into contact with quenching water within 5 to 60 seconds after the solution treatment process, and quenching is performed in a water tank for more than 5 minutes but not exceeding 40 minutes, 3. The method for producing an aluminum alloy forged product according to item 2 above, wherein the aging treatment step comprises heating the forged product after the quenching treatment step at a temperature of 180°C to 220°C for 0.5 hours to 8 hours to perform aging treatment. Effect of the Invention
[0017] According to the invention of [1], the alloy composition is limited, and the cross-sectional structure of an aluminum alloy forging is observed at a magnification of 1000 times in a field area of 1.5815 mm 2 By ensuring that the number of intermetallic compounds Mg2Si with minor axes of 0.5 μm or more present in the forging is 100 or less, it is possible to obtain an Al-Mg-Si-based aluminum alloy forging that has excellent mechanical properties at room temperature and is resistant to the generation of recrystallized grains.
[0018] According to the invention [2], a method for producing an Al-Mg-Si aluminum alloy forging having excellent mechanical properties at room temperature and being resistant to recrystallization grains can be provided.
[0019] According to the invention [3], it is possible to provide a method for producing an Al-Mg-Si aluminum alloy forging having even better mechanical properties at room temperature and being less susceptible to recrystallization grains. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is a perspective view showing an example of an aluminum alloy forging of the present invention. [Diagram 2]FIG. 2 is a SEM photograph showing the Mg2Si structure of the cross-sectional structure of the aluminum alloy forging in Example 1 taken by FE-SEM. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] FIG. 1 is a perspective view showing an example of an aluminum alloy forging of the present invention, and FIG. 2 is an SEM photograph showing the Mg2Si structure of a cross-sectional structure of the aluminum alloy forging in Example 1 taken by FE-SEM.
[0022] The aluminum alloy forged product and the manufacturing method thereof according to the present invention will be described in detail. Note that the following embodiments are merely examples, and the present invention is not limited to these embodiments, and may be modified as appropriate without departing from the technical concept of the present invention.
[0023] The aluminum alloy forging of the present invention contains 0.15% by mass to 1.0% by mass of Cu, 0.6% by mass to 1.3% by mass of Mg, 0.60% by mass to 1.45% by mass of Si, 0.03% by mass to 1.0% by mass of Mn, 0.2% by mass to 0.4% by mass of Fe, 0.03% by mass to 0.4% by mass of Cr, 0.012% by mass to 0.035% by mass of Ti, 0.0001% by mass to 0.03% by mass of B, a Zn content of 0.25% by mass or less, a Zr content of 0.05% by mass or less, and the balance being Al and unavoidable impurities. 2 The number of intermetallic compounds Mg2Si having a minor axis of 0.5 μm or more present in the steel sheet is 100 or less.
[0024] In the present invention, Mg2Si is an intermetallic compound, which precipitates in the structure of an aluminum alloy forging as shown in FIG. 2, and contributes to improving the strength of the aluminum alloy forging.
[0025] As shown in FIG. 2, in the aluminum alloy forging 1 of this embodiment, the cross-sectional structure was observed using an FE-SEM at a magnification of 1000 times, with a field area of 1.5815 mm 2 The number of intermetallic compounds Mg2Si with minor axes of 0.5 μm or more present in the structure is 100 or less.
[0026] In this embodiment, the cross-sectional structure of the aluminum alloy forging 1 is observed using an FE-SEM, but an electron microscope other than an FE-SEM may be used. Furthermore, the method is not limited to the use of an electron microscope, and any method can be used as long as it can observe the cross-sectional structure of the aluminum alloy forging 1 at a magnification of 1000 times.
[0027] According to the aluminum alloy forging of the present invention, in addition to the above-mentioned alloy composition, the cross-sectional structure of the aluminum alloy forging is observed at a magnification of 1000 times to have a visual field area of 1.5815 mm 2 By ensuring that the number of intermetallic compounds Mg2Si with minor axes of 0.5 μm or more present in the forging is 100 or less, it is possible to obtain an Al-Mg-Si-based aluminum alloy forging that has excellent mechanical properties at room temperature and is resistant to the generation of recrystallized grains.
[0028] Next, a method for producing an Al-Mg-Si aluminum alloy forging according to the present invention will be described.
[0029] The method for producing an aluminum alloy forged product of the present invention comprises a molten metal forming step, a casting step, a homogenizing heat treatment step, a forging step, a solution treatment step, a quenching treatment step, and an aging treatment step.
[0030] (Molten metal formation process) In the molten metal forming step, a molten metal of an aluminum alloy is obtained (prepared) containing Cu: 0.15 mass% to 1.0 mass%, Mg: 0.6 mass% to 1.3 mass%, Si: 0.60 mass% to 1.45 mass%, Mn: 0.03 mass% to 1.0 mass%, Fe: 0.2 mass% to 0.4 mass%, Cr: 0.03 mass% to 0.4 mass%, Ti: 0.012 mass% to 0.035 mass%, B: 0.0001 mass% to 0.03 mass%, Zn content is 0.25 mass% or less, Zr content is 0.05 mass% or less, and the balance is Al and inevitable impurities. In the aluminum alloy, the Zn content may be 0% (Zn-free) or the Zr content may be 0% (Zr-free).
[0031] (Casting process) The molten metal thus obtained is cast to obtain a cast product. The continuous casting method for obtaining the cast product is not particularly limited, but various known continuous casting methods (vertical continuous casting method, horizontal continuous casting method, etc.) can be used. As the vertical continuous casting method, a hot top casting method or the like is used.
[0032] In the following, a case where an aluminum alloy continuous cast material is produced by a hot top casting method using a hot top casting apparatus (i.e., a case where an aluminum alloy continuous cast material is produced by continuously casting a molten aluminum alloy by the hot top casting method) is briefly described as an example of a continuous casting method.
[0033] The hot top casting device is equipped with a mold, a molten metal receiving vessel (header), etc. The mold is cooled by cooling water that fills its interior. The receiving vessel is generally made of refractory material and is installed above the mold. The molten aluminum alloy in the receiving vessel is poured downward into the cooled mold, and is cooled and solidified at a predetermined cooling rate by the cooling water sprayed from the mold, and is further immersed in water (temperature: about 20°C) in a water tank where it solidifies completely. This produces long continuous cast material in the shape of a rod or the like.
[0034] (Homogenization heat treatment process) The resulting casting is subjected to homogenization heat treatment for 4 to 10 hours at a temperature of 370°C to 560°C. By carrying out homogenization heat treatment within this temperature range, the ingot is homogenized sufficiently and solute atoms are sufficiently dissolved, so that sufficient strength required for the subsequent aging treatment can be obtained.
[0035] (Forging process) In the forging process, the obtained ingot is forged at a heating temperature of 450°C to 560°C to obtain a forged product (such as a suspension arm part for an automobile). At this time, the starting temperature for forging the forging material is 450°C to 560°C. If the starting temperature is less than 450°C, the deformation resistance becomes high and sufficient processing becomes impossible, and if it exceeds 560°C, defects such as forging cracks and eutectic melting are likely to occur.
[0036] (Solution treatment process) The solution treatment process is a process for relieving the distortion introduced in the forging process and dissolving the solute elements. In this solution treatment process, the forged product is heated from 20°C to 500°C at a heating rate of 5.0°C / min or more, and then heated at 530°C to 560°C for 0.3 to 3 hours to perform solution treatment. If the treatment temperature is less than 530°C, the solution treatment does not progress and high strength cannot be achieved by aging precipitation. If the treatment temperature exceeds 560°C, the dissolution of the solute elements is further promoted, but eutectic melting and recrystallization are likely to occur.
[0037] (Quenching process) The quenching process is a heat treatment for rapidly cooling the solid solution state obtained by the solution treatment to form a supersaturated solid solution. After the solution treatment process, the entire surface of the forged product is brought into contact with quenching water within 5 to 60 seconds, and quenching is performed in a water tank for more than 5 minutes and less than 40 minutes.
[0038] (Aging treatment process) The forged product that has undergone the quenching process is then heated at a temperature of 180°C to 220°C for 0.5 to 8 hours to perform aging treatment. If the treatment temperature is less than 180°C or the treatment time is less than 0.5 hours, the Mg2Si-based precipitates that improve the tensile strength do not grow sufficiently, and if the treatment temperature exceeds 220°C, the Mg2Si-based precipitates become too coarse to sufficiently improve the tensile strength.
[0039] As described above, according to the method for manufacturing an aluminum alloy forging of the present invention, it is possible to provide a method for manufacturing an Al-Mg-Si aluminum alloy forging that has excellent mechanical properties at room temperature and is less susceptible to the generation of recrystallized grains.
[0040] Next, the composition of the "aluminum alloy" in the aluminum alloy forging and its manufacturing method according to the present invention will be described in detail below. The aluminum alloy contains 0.15% by mass to 1.0% by mass of Cu, 0.6% by mass to 1.3% by mass of Mg, 0.60% by mass to 1.45% by mass of Si, 0.03% by mass to 1.0% by mass of Mn, 0.2% by mass to 0.4% by mass of Fe, 0.03% by mass to 0.4% by mass of Cr, 0.012% by mass to 0.035% by mass of Ti, 0.0001% by mass to 0.03% by mass of B, 0.25% by mass or less of Zn, 0.05% by mass or less of Zr, and the balance being Al and unavoidable impurities.
[0041] Si coexists with Mg to form Mg2Si-based precipitates, which contribute to improving the strength of the final product. The Si content is preferably 0.60% by mass or more, since the strength of the final product after aging treatment is further increased by adding Si in excess of the amount that generates Mg2Si relative to the amount of Mg described below. On the other hand, if the Si content exceeds 1.45% by mass, the grain boundary precipitation of Si increases, grain boundary embrittlement is likely to occur, and not only does the plastic workability of the ingot and the toughness of the final product decrease, but the average grain size of the crystallized particles in the ingot may exceed a predetermined upper limit. Therefore, the Si content must be in the range of 0.60% by mass to 1.45% by mass.
[0042] Mg coexists with Si to form Mg2Si-based precipitates, which contribute to improving the strength of the final product. If the Mg content is less than 0.6 mass%, the effect of precipitation strengthening may be reduced. On the other hand, if the Mg content exceeds 1.3 mass%, not only may the plastic workability of the ingot and the toughness of the final product be reduced, but the average grain size of the crystallized particles in the ingot may exceed a predetermined upper limit. Therefore, the Mg content must be in the range of 0.6 mass% to 1.3 mass%.
[0043] Cu increases the apparent supersaturation amount of Mg2Si-based precipitates, and increases the amount of Mg2Si precipitates, thereby significantly promoting the age hardening of the final product. If the Cu content is less than 0.15 mass%, the Q phase (Al-Cu-Mg-Si), which is effective for precipitation strengthening, is difficult to form, resulting in a decrease in mechanical properties. On the other hand, if the Cu content exceeds 1.0 mass%, the forgeability of the ingot and the toughness of the final product may decrease, and further the corrosion resistance may decrease significantly. Therefore, the Cu content must be in the range of 0.15 mass% to 1.0 mass%.
[0044] Mn crystallizes as an AlMnSi phase, and Mn that does not crystallize precipitates and suppresses recrystallization. This effect of suppressing recrystallization makes the crystal grains fine even after plastic processing, and improves the toughness and corrosion resistance of the final product. If the Mn content is less than 0.03 mass%, the above-mentioned effects may be reduced. On the other hand, if it exceeds 1.0 mass%, giant intermetallic compounds may be generated, and the ingot structure of the present invention may not be satisfied. Therefore, the Mn content must be in the range of 0.03 mass% to 1.0 mass%.
[0045] Cr also crystallizes as an AlCrSi phase, and Cr that does not crystallize precipitates and suppresses recrystallization. This effect of suppressing recrystallization makes the crystal grains fine even after plastic processing, and improves the toughness and corrosion resistance of the final product. If the Cr content is less than 0.03 mass%, the above-mentioned effects may be reduced. On the other hand, if the Cr content exceeds 0.4 mass%, giant intermetallic compounds may be generated, and the ingot structure of the present invention may not be satisfied. Therefore, the Cr content must be in the range of 0.03 mass% to 0.4 mass%.
[0046] Fe combines with Al and Si to crystallize in the alloy, and prevents grain coarsening. If the Fe content is less than 0.2 mass%, the above effects may not be obtained. If the Fe content exceeds 0.4 mass%, coarse intermetallic compounds may be generated, and the plastic workability may deteriorate. Therefore, the Fe content must be 0.2 mass% to 0.4 mass%.
[0047] Zn is treated as an impurity, and if it exceeds 0.25 mass %, it accelerates the corrosion of aluminum itself and deteriorates the corrosion resistance, so the content must be 0.25 mass % or less.
[0048] Zr is treated as an impurity, and if it exceeds 0.05 mass%, the grain refining effect of the Al-Ti-B alloy is weakened, resulting in a decrease in the strength of the processed product after plastic working, so the content must be 0.05 mass% or less.
[0049] Ti is an alloying element effective in refining crystal grains, and also prevents the occurrence of ingot cracks in continuously cast rods. If the Ti content is less than 0.012% by mass, the refining effect is not obtained, while if it exceeds 0.035% by mass, coarse Ti compounds may crystallize, deteriorating toughness. Therefore, the Ti content must be in the range of 0.012% to 0.035% by mass.
[0050] Like Ti, B is also an element effective in refining crystal grains, and if its content is less than 0.0001 mass%, the effect is not obtained, while if its content exceeds 0.03 mass%, there is a risk of the toughness being deteriorated. Therefore, the B content must be in the range of 0.0001 mass% to 0.03 mass%. EXAMPLES
[0051] Next, specific examples of the present invention will be described, but the present invention is not particularly limited to these examples.
[0052] <Examples 1 to 12> A continuous cast material having a circular cross section with a diameter of 54 mm was produced from an aluminum alloy having the alloy composition shown in Table 1, which was then subjected to homogenization heat treatment under the conditions shown in Table 1 and air-cooled. The resulting cast material was forged under the conditions shown in Table 1 and plastically worked into the shape of an automobile suspension arm part shown in Figure 1. Next, solution treatment was performed under the conditions shown in Table 1, followed by quenching treatment under the conditions shown in Table 1, and then aging treatment under the conditions shown in Table 1 to obtain aluminum alloy forging 1.
[0053] <Comparative Examples 1 to 5> A continuous cast material having a circular cross section with a diameter of 54 mm was produced from an aluminum alloy having the alloy composition shown in Table 2, which was then subjected to homogenization heat treatment under the conditions shown in Table 2 and air-cooled. The resulting cast material was forged under the conditions shown in Table 2 and plastically worked into the shape of an automobile suspension arm part shown in Figure 1. Next, solution treatment was performed under the conditions shown in Table 2, followed by quenching treatment under the conditions shown in Table 2, and then aging treatment under the conditions shown in Table 2 to obtain an aluminum alloy forging.
[0054] [Table 1]
[0055] [Table 2]
[0056] Each of the aluminum forged products obtained as described above was evaluated according to the following evaluation methods. The results are shown in Tables 1 and 2.
[0057] The "number of Mg2Si" in Tables 1 and 2 is the number present in the matrix of each aluminum alloy forging. A sample piece for microstructural observation measuring approximately 10 mm x 10 mm x 10 mm was cut from the center of the thickest part of the obtained aluminum alloy forging, and this sample piece was polished using a cross section polisher. Then, as shown in Figure 2, an FE-SEM photograph (field emission scanning electron microscope photograph, magnification 1000 times) of this polished sample piece was taken, and the field of view area in this SEM photograph was 1.5815 mm2. 2 The number of Mg2Si particles with a minor axis of 0.5 μm or more that existed within the range was determined (evaluated).
[0058] <Method for evaluating tensile strength at room temperature> Tensile test pieces having a gauge length of 25.4 mm and a parallel part diameter of 6.4 mm were taken from the obtained aluminum alloy forgings, and room temperature (25°C) tensile tests were performed on the tensile test pieces to measure the room temperature tensile strength and evaluate it based on the following criteria. (Judgment criteria) "◎": Yield strength at room temperature is 360 MPa or more "○": Yield strength at room temperature is 340 MPa or more and less than 360 MPa "△": Yield strength at room temperature is 320MPa or more but less than 340MPa "X": The yield strength at room temperature is less than 320 MPa.
[0059] As is clear from the table, the aluminum alloy forgings of Examples 1 to 12 produced by the production method of the present invention were excellent in tensile strength at room temperature, and had 100 or less Mg2Si particles.
[0060] In contrast, the aluminum alloy forged products of Comparative Examples 1 to 5, which deviate from the range specified by the present invention, were inferior in tensile strength at room temperature. [Industrial Applicability]
[0061] The forged products obtained by the method for producing aluminum alloy forged products according to the present invention have excellent mechanical strength at room temperature and are therefore suitable for use, for example, as suspension parts such as suspension arm parts for automobiles, although they are not particularly limited to such applications. [Explanation of symbols]
[0062] 1: Aluminum alloy forgings
Claims
1. An aluminum alloy forging containing 0.15 mass% to 1.0 mass% Cu, 0.6 mass% to 1.3 mass% Mg, 0.60 mass% to 1.45 mass% Si, 0.03 mass% to 1.0 mass% Mn, 0.2 mass% to 0.4 mass% Fe, 0.03 mass% to 0.4 mass% Cr, 0.012 mass% to 0.035 mass% Ti, and 0.0001 mass% to 0.03 mass% B, with a Zn content of 0.25 mass% or less, a Zr content of 0.05 mass% or less, and the balance being Al and unavoidable impurities, The cross-sectional structure of the aluminum alloy forged product was observed at a magnification of 1000 times to obtain a field area of 1.5815 mm 2 Intermetallic compounds with minor axes of 0.5 μm or more that exist in 2 An aluminum alloy forging, characterized in that the number of Si particles is 10 or more and 100 or less.
2. A method for producing an aluminum alloy forged product according to claim 1, a molten metal forming step for obtaining a molten metal; a casting step of obtaining a casting by casting the molten metal obtained in the molten metal forming step; a homogenization heat treatment step in which homogenization heat treatment is performed on the casting obtained in the casting step; A forging process for obtaining a forged product by forging the cast product after the homogenization heat treatment process; a solution treatment step of subjecting the forged product obtained in the forging step to a solution treatment; a quenching treatment step of quenching after the solution treatment step; and an aging treatment step of subjecting the forged product after the quenching treatment step to aging treatment.
3. The homogenization heat treatment step is a homogenization heat treatment step in which the casting obtained in the casting step is held at a temperature of 370°C to 560°C for 4 hours to 10 hours, The forging process is a process of forging the casting after the homogenization heat treatment process at a heating temperature of 450°C to 560°C. The solution treatment step is a step of heating the forged product obtained in the forging step from 20°C to 500°C at a heating rate of 5.0°C / min or more, and then holding the product at 530°C to 560°C for 0.3 hours to 3 hours. In the quenching treatment step, the entire surface of the forged product is brought into contact with quenching water within 5 to 60 seconds after the solution treatment step, and quenching is performed in a water tank for more than 5 minutes but not exceeding 40 minutes.
3. The method for manufacturing an aluminum alloy forged product according to claim 2, wherein the aging treatment step comprises heating the forged product after the quenching treatment step at a temperature of 180°C to 220°C for 0.5 hours to 8 hours for aging treatment.
Citation Information
Patent Citations
High-strength Al-Mg-Si-Cu alloy and preparation method thereof
CN102337429A
Aluminum alloy for forging
JP1993059477A
Production of aluminum alloy for forging and forged product of aluminum alloy
JP1993247574A
Aluminum alloy cast member for forging
JP1994256880A
High strength and high toughness aluminum alloy forged material excellent in corrosion resistance
JP2001107168A